Trauma and aggression: Evaluating the influence of primed hostility and survivor sex. (8th August 2022) - Ripley, Adam J.; Clapp, Joshua D.; Wilkowski, Benjamin M.
Abstract: Objectives: The relation between posttrauma symptoms and aggression is an area of growing interest in the larger clinical literature. The current project looked to examine the impact of primed hostility on aggressive responding in men and women with and without a history of prior trauma. Design: Experimental aggression paradigm assessed in a 2 (Group) × 2 (Sex) × 2 (Prime) mixed factorial ANOVA. Methods: Trauma‐naïve participants ( N = 52) and survivors reporting active symptoms ( N = 43) were exposed to hostile and neutral lexical primes in what was presented as a reaction time task played against an unseen 'opponent'. In actuality, 'wins' and 'losses' during the task were assigned by an automated system. The intensity of an aversive sound blast delivered by participants to the supposed opponent in trials the participant 'won' served as an index of behavioural aggression. Results: Repeated‐measures ANOVA identified a between‐by‐within interaction of exposure group and lexical prime ( p = .010; η p 2 = .070), with trauma‐exposed participants ( p = .002, Δ = .30), but not controls ( p = .159, Δ = .11), demonstrating elevations in aggression subsequent to hostile priming. A sex by prime interaction ( p = .001; η p 2 = .117) similarly indicated elevated aggression following hostile priming in men ( p = .007, Δ = .58) as compared to women ( p = .062, Δ = .10). Conclusions: Results offer preliminary support for the association of situationally primed hostility and biological sex with aggressive responding in survivors reporting active symptoms.